Alcohol Control by Referendum in Northern Native Communities: The Alaska Local Option Law - Berman, Matthew; Hull, Theresa (ARCTIC, 2001)
When Alaska became a state in 1959, state laws took control of alcohol regulation from the federal government and Native communities. In 1981, however, the state legislature changed the alcohol laws to give residents broad powers, via a local option referendum, to regulate how alcohol comes into their communities. By mid-1999, 112 small communities had held nearly 200 alcohol control elections under the state law. Of these elections, 69% added new restrictions on alcohol, while 13% removed restrictions previously imposed. The remaining 18% did not receive the majority vote needed to change the existing status. Most communities passing local option restrictions chose to ban sale and importation of alcohol. Although most of these elections occurred during the first eight years after the law was passed, elections continue to occur as the law evolves and as communities debate the merits of alcohol control. Growing evidence suggests that the local option law may reduce adverse effects of alcohol abuse in Alaska Native communities. However, the law's most important contribution may be to restore a limited form of self-government to these communities. Quand l'Alaska est devenu un État en 1959, les lois nationales ont retiré au gouvernement fédéral et aux communautés autochtones le contrôle des règlements concernant l'alcool. En 1981, cependant, l'Assemblée législative nationale a modifié les lois sur les boissons alcoolisées en vue de donner aux résidents, par le biais d'un référendum sur l'option locale, des pouvoirs étendus sur l'entrée de l'alcool dans leurs communautés. Au milieu des années 1999, l12 petites communautés avaient tenu près de 200 élections sur la régie de l'alcool en vertu de la loi nationale. De ces élections, 69 p. cent ajoutaient de nouvelles restrictions sur les boissons alcoolisées, tandis que 13 p. cent enlevaient des restrictions imposées précédemment. Les 18 p. cent restant n'ont pas reçu le vote majoritaire nécessaire pour changer la situation en place. La plupart des communautés qui ont ...